(untitled) (El Taco en la Brea, 2019)
Los girasoles ciegos (2004) written by Alberto Méndez, was published in the context of a memorial boom in Spain, characterized by the events of the civil war and its aftermath. The purpose of this paper is to analyze, at first, the polysemic word «derrota», which Méndez uses to name the four short stories of the book, and later, to examine the role played by this word in the construction of collective memory. This volume will not be approached as a historical reconstruction, but rather as an intervention in the traumatic memory of defeat. This paper will thus develop how Los girasoles ciegos illustrates the need of a grieving process and a forgiveness scene.